Cognitive Control, Cognitive Biases and Emotion Regulation in Depression: A New Proposal for an Integrative Interplay Model - Villalobos, Dolores; Pacios, Javier; Vázquez, Carmelo (Frontiers in Psychology, 2021)
Research traditions on cognition and depression focused on relatively unconnected aspects of cognitive functioning. The neuropsychological perspective has concentrated on cognitive control (CC) difficulties as a prominent feature of this condition. A review of the literature was performed focus on each component of CC. These difficulties are observables and more evident for mood-congruent materials, suggesting that cognitive biases interact with CC difficulties to hinder cognitive switching, working memory updating and inhibition of irrelevant information. From a clinical psychology perspective, the emphasis on cognitive aspects has focused on processing information biases for emotional information as well as on the existence of repetitive negative patterns of thinking (i.e. rumination). Connecting research from these two traditions, we propose a novel integrative cognitive model of depression, where the interplay between CC difficulties, rumination, and cognitive biases lead to ineffective emotion regulation strategies to downregulate negative mood and upregulate positive mood.